Prevalence of premorbid metabolic syndrome in Spanish adult workers using IDF and ATPIII diagnostic criteria: relationship with cardiovascular risk factors. - Pedro Tauler; Miquel Bennasar-Veny; Jose M Morales-Asencio; Angel A Lopez-Gonzalez; Teofila Vicente-Herrero; Joan De Pedro-Gomez; Vanessa Royo; Jordi Pericas-Beltran; Antoni Aguilo (PLoS ONE)
Background Metabolic Syndrome (MetS) is a complex disorder defined as a cluster of interconnected risk factors such as hypertension, dyslipidemia, obesity and high blood glucose levels. Premorbid metabolic syndrome (PMetS) is defined by excluding patients with previously diagnosed cardiovascular disease or diabetes mellitus from those suffering MetS. We aimed to determine the prevalence of PMetS in a working population, and to analyse the relationship between the diagnostic criteria of the International Diabetes Federation (IDF) and of the National Cholesterol Education Program Adult Treatment Panel III (ATPIII). The relationship between the presence of PMetS and cardiovascular risk factors was also analysed. Research methodology/findings A cross-sectional study was conducted in 24,529 male and 18,736 female Spanish (white western European) adult workers (20-65 years) randomly selected during their work health periodic examinations. Anthropometrics, blood pressure and serum parameters were measured. The presence of MetS and PMetS was ascertained using ATPIII and IDF criteria. Cardiovascular risk was determined using the Framingham-REGICOR equation. The results showed MetS had an adjusted global prevalence of 12.39% using ATPIII criteria and 16.46% using IDF criteria. The prevalence of PMetS was slightly lower (11.21% using ATPIII criteria and 14.72% using IDF criteria). Prevalence in males was always higher than in females. Participants with PMetS displayed higher values of BMI, waist circumference, blood pressure, glucose and triglycerides, and lower HDL-cholesterol levels. Logistic regression models reported lower PMetS risk for females, non-obese subjects, non-smokers and younger participants. Cardiovascular risk determined with Framingham-REGICOR was higher in participants with PMetS. Conclusions PMetS could be a reliable tool for the early identification of apparently healthy individuals who have a significant risk for developing cardiovascular events and type 2 diabetes.